Scanning pattern angle effect on the resulting properties of selective laser sintered monolayers of Cu-Sn-Ni powder. (January 2018) - Sabelle, Matías; Walczak, Magdalena; Ramos-Grez, Jorge
Highlights: Effect of laser scanning pattern angle, speed and power during the SLS of a commercial Cu-Sn-Ni alloy in the form of monolayers was studied. Monolayer fabrication at the vicinity of a scan angle of 60° resulted in higher density layers with maximum mechanical strength. Understanding of the SLS process of a monolayer can provide insight on the results of the corresponding volumetric process. Laser based metal additive manufacturing users would benefit from reading these results and analysis. Abstract: Laser–based layer manufacturing of metals, also known as additive manufacturing, is a growing research field of academic and industrial interest. However, in the associated laser–driven processes (i.e. selective laser sintering (SLS) or melting (SLM)), optimization of some parameters has not been fully explored. This research aims at determining how the angle of laser scanning pattern (i.e. build orientation) in SLS affects the mechanical properties and structure of an individual Cu-Sn-Ni alloy metallic layer sintered in the process. Experiments consist in varying the angle of the scanning pattern (0°, 30°, 45° 60° and 90° relative to the transverse dimension of the piece), at constant scanning speed and laser beam power, producing specimens of different thicknesses. A noticeable effect of the scan angle on the mechanical strength and degree of densification of the sintered specimens is found. Thickness of the resulting monolayer correlates negatively with increasing scan angle, whereas relative density correlates positively. A minimum porosity and maximum UTS are found at the angle of 60°. It is concluded that angle of the scanning pattern angle plays a significant role in SLS of metallic monolayers.